Heydar Aliyev and the Foundations of Modern Azerbaijan
XII, 348 p. 1 illus.
Keywords: “This groundbreaking study stands as the foremost exploration of Heydar Aliyev’s vision and policies, illuminating the remarkable reconstruction of Azerbaijan and the establishment of its modern state institutions. This is not just a book; it’s a key to unravelling the roots of today’s prosperous Azerbaijani state and society. An essential read for those seeking profound insights into Azerbaijan's journey of transformation.” – Hikmet Cetin, Former Foreign Minister of Turkey. “This book delves into Aliyev’s multifaceted legacy – political, economic, and social. An invaluable resource for academia and the wider audience, it provides crucial insights into the strategically vital country and its international relations, both regionally and with major powers, during a pivotal period in world history.” – Michael B. Bishku, Professor Emeritus of History, Augusta University, Georgia, USA. This edited book examines and analyses Heydar Aliyev, the architect and founder of modern, post-Soviet Azerbaijan. The editors of the volume discuss developments between 1993 and 2003 – a decade that saw the establishment of the institutional foundations of the current republic, the adoption of a new form of national identity, the redefinition of the concept of the Azerbaijani state, and the creation of a security establishment designed to gain control of territories Armenia had held since the 1988-1994 war over Karabakh. The book explains why this fateful period had far-reaching consequences for Azerbaijan as a fully formed state and society, as well as major implications for its political future and its geopolitical strategy. M. Hakan Yavuz is Professor of Political Science at the University of Utah, USA. Michael M. Gunter is Professor of Political Science at Tennessee Technological University in Cookeville, Tennessee, USA. Shamkhal Abilov is Lecturer in the International Relations Department at Baku Engineering University, Azerbaijan.